Impact of Heat Stress on Physiological Characteristics, Blood Constituents and HSP Genes Expression in Mithun during Summer Season - Chowlu, Homseng; Vidyarthi, V. K.; Mukherjee, S. (International Journal of Bio-resource and Stress Management, 2023)
Six healthy Mithun animals being reared in the shade and were not exposed to sunlight in the morning hours were termed as control group (T1). The same animals were exposed to sunlight from 6.00 am to 2.00 pm to induce heat stress and were termed as the heat stressed group (T2). The samples for observations on physiological, blood constituents and gene expression were recorded at 6.00 am (T1) and 2.00 pm (T2). The values for physiological characteristics, viz., rectal temp (100.04±0.26 vs 103.34±0.20), respiration rate per minute (26.67±0.52 vs 33.00±0.74) and pulse rate per minute (42.44±1.02 vs 59.83±0.84) were significantly (P<0.05) higher in the heat stressed group than non stress group. The values for blood constituents viz., glucose (50.82±1.27 vs 60.09±1.46), SGOT (44.91±0.89 vs 51.18±1.08), SGPT (44.17±0.87 vs 49.92±0.87), cortisol (712.48±0.03 vs 712.49±0.02) and THI (77.56±0.39 vs 81.42±3.40) were also significantly (p<0.05) higher in the heat stress group than non stress group. The values for expression of HSP 70 gene (28.24 ±0.15 vs 28.88±0.59) and HSP 90 gene (36.13±1.24 vs 35.87±1.90) were also significantly (p<0.05) higher in the heat stressed group of Mithun than non stress group. The results of the study revealed that summer heat stress had a significant effect in Mithun.